Filmes de PAH/PAA com nanopartículas metálicas para a desinfecção de efluentes industriais - Eltz, Fabiana Zarpelon (My University, 2018)
The supply and access to drinking water is one of the great challenges of this century. In this perspective, the rapid advancement of Nanotechnology has contributed significantly to the development and production of nanomaterials, aiming to improve the performance and efficiency of water decontamination processes. Thus, the main goal of this work was to prepare and characterize self-assembled thin films of poly(allylamine hydrochloride) (PAH) and poly(acrylic acid) (PAA) containing silver nanoparticles (AgNPs) and copper (CuNPs) for their subsequent application in the tertiary treatment of industrial effluents for reuse. The AgNPs and CuNPs were synthesized by (i) reducing silver and copper (II) salts in aqueous medium, with subsequent incorporation in PAH/PAA thin films, and (ii) by direct irradiation of the PAH/PAA thin films with ultraviolet (UV) light after immersion in silver and copper (II) salt solutions. After self-assembling, the thin films were characterized by different instrumental techniques, including ultraviolet and visible (UV-Vis) molecular absorption spectroscopy, glow discharge optical emission spectroscopy (GD-OES), atomic force microscopy (AFM), field emission scanning electron microscopy (FESEM), X-ray photoelectron spectroscopy (XPS), inductively coupled argon plasma optical emission spectroscopy (ICP-OES) and transmission electron microscopy (TEM). In general, the UV-Vis and GD-OES spectra confirmed the incorporation/formation of AgNPs and CuNPs/copper (II) oxide in the thin films. The tests carried out with the industrial effluent showed that all the films developed presented bactericidal activity against total coliforms, ranging from 14 to 100% in terms of inhibition. The films containing AgNPs, by other hand, presented bactericidal activity 5% higher when compared to the films containing CuNPs. In addition, the films prepared from direct irradiation with UV light showed the highest inhibitory efficiency (greater than 90%) and, therefore, were evaluated as a function of the variation of the precursor salt concentration. In general, it was observed through the characterization by FESEM and TEM that the change in salt concentration promoted a variation in terms of size incorporated into the films (10-250 nm for AgNPs and 10-170 nm for CuNPs). The treatment of the industrial effluent for reuse with the films obtained by method (ii), in turn, reduced the total count of coliforms present in the raw industrial effluent (untreated) from 91 to 100%, being that the film obtained at the concentration 0.1098 mmol/L Ag+ was the most efficient material. Finally, considering the ease of application, the low environmental impact, and the satisfactory inhibitory action, the films developed in this work present a great potential to be used as auxiliaries in the tertiary treatment of industrial effluents.
O fornecimento e o acesso à água potável é um dos grandes desafios deste século. Nesta perspectiva, o rápido avanço da Nanotecnologia tem contribuído significativamente para o desenvolvimento e a produção de nanomateriais, objetivando melhorar o desempenho e a eficiência dos processos de descontaminação da água. Desse modo, o presente trabalho teve por objetivo preparar e caracterizar filmes automontados de poli(hidrocloreto de alilamina) (PAH) e poli(ácido acrílico) (PAA) contendo nanopartículas de prata (AgNPs) e de cobre (CuNPs), visando sua posterior aplicação no tratamento terciário de efluentes industriais para reuso. As AgNPs e CuNPs foram sintetizadas por meio da (i) redução de sais de prata e de cobre (II) em meio aquoso, com posterior incorporação das mesmas nos filmes finos de PAH/PAA, e (ii) pela irradiação direta dos filmes finos de PAH/PAA com luz ultravioleta (UV), após a imersão dos mesmos em soluções salinas de prata e cobre (II). Após a automontagem, os filmes foram caracterizados por meio de diferentes técnicas instrumentais, incluindo a espectroscopia de absorção molecular na região do ultravioleta e visível (UV-Vis), a espectroscopia de emissão óptica por descarga luminescente (GD-OES), a microscopia de força atômica (AFM), a microscopia eletrônica de varredura com emissão de campo (MEV-FEG), a espectroscopia de fotoelétrons excitados por raios X (XPS), a espectrometria de emissão óptica com plasma de argônio indutivamente acoplado (ICP-OES) e a microscopia eletrônica de transmissão (MET). De maneira geral, os espectros de UV-Vis e GD-OES comprovaram a incorporação/formação de AgNPs e de CuNPs/óxido de cobre (II) nos filmes finos desse trabalho. Os testes realizados com o efluente industrial evidenciaram que todos os filmes desenvolvidos apresentaram atividade bactericida frente a coliformes totais, com variação de 14 a 100% em termos de inibição. Os filmes contendo AgNPs, por sua vez, apresentaram atividade bactericida 5% superior, quando comparados aos filmes contendo CuNPs. Além disso, os filmes preparados a partir da irradiação direta com luz UV apresentaram a maior eficiência inibitória (superior a 90%) e, dessa forma, foram avaliados em função da variação da concentração do sal precursor. De maneira geral, observou-se através da caracterização por MEV-FEG e MET que a alteração na concentração do sal promoveu uma variação em termos de tamanho das nanopartículas incorporadas aos filmes (10-250 nm para as AgNPs e 10-170 nm para as CuNPs). O tratamento do efluente industrial para reuso com os filmes obtidos pelo método (ii), por sua vez, reduziu de 91 a 100% a contagem total de coliformes presentes no efluente industrial bruto (sem tratamento), sendo que o filme obtido na concentração 0,1098 mmol/L de Ag+ foi o material com maior eficácia. Finalmente, considerando-se a facilidade de aplicação, o baixo impacto ambiental, e a ação inibidora satisfatória, os filmes desenvolvidos neste trabalho apresentam um grande potencial para serem utilizados como auxiliares no tratamento terciário de efluentes industriais.
Keywords: Nanopartículas; Filmes finos; Prata; Cobre; Resíduos industriais; Nanoparticles; Thin films; Silver; Copper; Factory and trade waste